KEMAMPUAN LITERASI SAINS MAHASISWA PENDIDIKAN IPA UNIMED: EVALUASI INFORMASI DI ERA AI BERBASIS PISA 2025 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the scientific literacy capabilities of Science Education students at Universitas Negeri Medan in evaluating scientific information in the Artificial Intelligence (AI) era using the PISA 2025 framework. The research method employed was quantitative descriptive involving 72 students selected via simple random sampling. Data collection utilized a scientific literacy test adapted for the AI-based learning context, covering aspects of knowledge, reasoning, and information evaluation. The results showed the students' average scientific literacy score was 57.66 (moderate category) with a left-skewed data distribution. Although students were capable of interpreting basic scientific data, they experienced significant difficulties in the aspects of evaluating and designing scientific inquiry and validating the credibility of digital sources. There is a distinct gap between high usage of AI tools and low critical verification capabilities regarding the generated outputs. The conclusion emphasizes that students' abilities remain operational digital rather than epistemologically evaluative. Therefore, strengthening critical AI literacy and authentic inquiry approaches in lectures is necessary to enhance the readiness of prospective science teachers in facing misinformation challenges in the digital era.